IL MUSEO PAOLO ORSI DI SIRACUSA. UN PROGETTO PILOTA CON GOOGLE. Virtual tour a 360° del museo e di reperti archeologici in modalità Street View - Bonacini, Elisa; Monterosso, Giuseppina (Archeomatica, 2016)
The aim of this paper is to offer a preview of the pilot project at the "Paolo Orsi” Regional Archaeological Museum of Syracuse (Italy). Thanks to a free partnership with Google Business Photos/Street View Indoor, we managed to map the entire museum, the only archaeological museum in South Italy that can be visited online on a 360° tour on a Google platform, with a dozen archaeological finds which can be clicked as POIs from the museum windows and explored, taking 360° virtual tours, provided with descriptive sheets. The aim of the project is is to begin to bridge the gap of Sicilian Cultural Heritage's visibility on the web.